ANALISIS KINERJA PEMERINTAH DESA DENGAN PENDEKATAN KUANTITATIF DAN KUALITATIF (STUDI PADA DESA DI KECAMATAN INGIN JAYA KABUPATEN ACEH BESAR) - Sari, Rahmi; Indriani, Mirna (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
Performance measurement is a method or device used to record and assess the achievement of implementing the activities based on the goals, objectives and strategies. The purpose of this study is to determine the financial performance and seen from the aspect economic, efficiency and effectiveness and to know non-financial performance seen from the aspect of achieving the goals felt by the community. This Study uses primary data from the results of village and community aparatusinterviews and uses secondary data in the form of Accountability Report Realization Implementation Budget Revenue and Expenditure Village. The result showed that the measurement of financial performance using the concept of value for money is considered unsuitable to measure the financial performance of village local government. Meanwhile, non-financial performance measurement result based on the priority use of village development funds have been successfully achieved by the village goverment, while the priority of the use of village government. Overall the are still some villages that do activities in the field of the development and community empowerment beyond the priority of the use of village funds that have been set.